2018
DOI: 10.1002/cctc.201800398
|View full text |Cite
|
Sign up to set email alerts
|

Tracking the Active Catalyst for Iron‐Based Ammonia Decomposition by In Situ Synchrotron Diffraction Studies

Abstract: Iron‐based catalysts for NH3 decomposition have been studied by a combination of catalytic tests and in situ synchrotron diffraction experiments performed in an inert sapphire plug‐flow cell. In contrast to steel‐based reaction cells, sapphire or quartz glass cells show no blind activity. Starting from iron oxide precursors, iron nitrides form during the activation cycle. Nitrides remain as main crystalline phases and govern the conversion of NH3 decomposition in the subsequent cycles. In this work structural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 60 publications
0
14
0
1
Order By: Relevance
“…Through in situ experiments, Tseng et al claimed that the active form of catalysts composed of Fe is Fe 3 N x , while at high temperatures (>675 °C) FeN x is formed, which has a negative influence on ammonia conversion. A Fe 2 O 3 catalyst supported on SBA-15 mesoporous silica shows better catalytic activity than the bare iron oxide (18 vs 4% at 500 °C) . Pelka et al observed that the catalytic decomposition reaction rate of ammonia is higher in the case of nanocrystalline iron compared to iron nitride Fe 4 N. The decrease of ammonia conversion in the presence of Fe 4 N has also been evidenced with a Fe catalyst promoted with Al 2 O 3 , CaO, and K 2 O with or without SiO 2 . Temperature influences the degree of nitriding, being favored at temperatures above 400 °C .…”
Section: Catalysts For the Thermal Decomposition Of Ammoniamentioning
confidence: 99%
See 1 more Smart Citation
“…Through in situ experiments, Tseng et al claimed that the active form of catalysts composed of Fe is Fe 3 N x , while at high temperatures (>675 °C) FeN x is formed, which has a negative influence on ammonia conversion. A Fe 2 O 3 catalyst supported on SBA-15 mesoporous silica shows better catalytic activity than the bare iron oxide (18 vs 4% at 500 °C) . Pelka et al observed that the catalytic decomposition reaction rate of ammonia is higher in the case of nanocrystalline iron compared to iron nitride Fe 4 N. The decrease of ammonia conversion in the presence of Fe 4 N has also been evidenced with a Fe catalyst promoted with Al 2 O 3 , CaO, and K 2 O with or without SiO 2 . Temperature influences the degree of nitriding, being favored at temperatures above 400 °C .…”
Section: Catalysts For the Thermal Decomposition Of Ammoniamentioning
confidence: 99%
“…297 The same behavior was obtained with a reference catalyst composed only of Fe 2 O 3 . 297 Through in situ experiments, Tseng et al 298 claimed that the active form of catalysts composed of Fe is Fe 3 N x , while at high temperatures (>675 °C) FeN x is formed, which has a negative influence on ammonia conversion. A Fe 2 O 3 catalyst supported on SBA-15 mesoporous silica shows better catalytic activity than the bare iron oxide (18 vs 4% at 500 °C).…”
mentioning
confidence: 99%
“…Considering the high reaction temperature and also technical/safety aspects related to ammonia may be quite challenging aspects for future investigations. Nevertheless, Tseng et al [77] were already able to observe the temperature-sensitive evolution of active nitrogenrich Fe 3 N x species during ammonia decomposition on iron catalysts via in situ X-ray diffraction. Moreover, Kirste et al [78] were able to observe different oxidation states and bimetallic interactions of CoÀ Re catalysts using in situ EXAFS and XANES experiments.…”
Section: Figurementioning
confidence: 99%
“…53 In consequence, diffusive NH 3 transport is expected to occur inside the fibers and along with the fiber-coating interface. Ammonia diffusing though the carbon fiber readily reacts with iron oxide precipitates along with the contact to the ceramic layer to either directly form Fe-based nitrides 55 or, if carbon is present, carbothermal reduction nitridation takes place. 56 N (g) + C (s) + Fe 𝑥 O (s) → Fe 𝑥 N (s) + CO (g)…”
Section: Fiber-coating Interfacementioning
confidence: 99%
“…At 1000 • C, the ε-Fe x N precipitates have not only withstood reduction but also undergone considerable growth compared to the sample prepared at 700 • C, while FeO enclosed in the ceramic layer has been reduced to α-iron by either CO or H 2 . According to Equation (1), ammonia decomposes due to both elevated temperature 43,44 and catalytic conversion at ε-Fe x N sites, 55 likely generating H 2 and N 2 inside the fiber. Hydrogen diffuses through the fiber, whereas N 2 is retained presumably resulting in a locally increased nitriding potential.…”
Section: Fiber-coating Interfacementioning
confidence: 99%